The endogenous money hypothesis: empirical evidence from Türkiye (2008-2020) - BOLKOL, HAKKI KUTAY (My University, 2024)
This paper examines the validity of the endogenous money supply hypothesis in Türkiye from 2008 to 2020. The endogenous money hypothesis underlines the fact that a demand for bank credit leads to the creation of credit and deposit. Deposits are created once credit application is approved by banks. Therefore, the money supply is endogenously determined by bank loans. However, there exist horizontalist, structuralist, and circuitist views, each proposing different causalities between monetary aggregates and the relationship between money and income. In this article, we put forth ten hypotheses to test the validity of the endogenous money hypothesis and three main perspectives over the period 2008-2020 in Türkiye. We aim to discern which of the three main views aligns best with the sample. Our findings provide new evidence on the validity of the endogenous money hypothesis in Türkiye from 2008 to 2020. Besides, the circuit theory of money fits precisely in the short run but partially in the long run. The findings also support the structuralist view partially according to the long-run results.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Social Sciences and Humanities; Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities